G‐quadruplex ligands inhibit chikungunya virus replication. Issue 6 (2nd February 2022) - Lv, Lu; Cui, Haoran; Chen, Zhiyang; Zhou, Yixuan; Zhang, Leiliang
Abstract: Chikungunya virus (CHIKV) is a mosquito‐transmitted alphavirus affecting human health globally. G‐quadruplex secondary structures attract great attention as potential targets for antiviral strategy. In this study, we show that the CHIKV genome possesses several conserved potential G‐quadruplex sequences. G‐quadruplex ligands BRACO‐19 and TMPyP4 could stabilize the CHIKV G‐quadruplex and inhibit the transcription of constructs containing CHIKV G‐quadruplex sequences. Importantly, BRACO‐19 and TMPyP4 suppress CHIKV replication. Our study not only reinforces the presence of viral G‐quadruplex sequences but also suggests that targeting G‐quadruplex structure could represent a novel strategy to inhibit CHIKV. Highlights: CHIKV possesses conserved G‐quadruplexes G‐quadruplex ligands stabilize CHIKV G‐quadruplexes with high affinities G‐quadruplex structures reduce the transcription of the GFP reporter gene containing CHIKV G‐quadruplex G‐quadruplex ligands BRACO‐19 and TMPyP4 inhibit CHIKV replication